(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Dignity and Trust in the Organizational Environment of Romanian Schools The speciality literature was preoccupied in the last years more and more of what it means the belief in organisation and the implications that makes them on employees and implicit on companies. The interpersonal confidence is a psychological feature that is developed in time as a result of exchangeable social process. Building the confidence is an activity that can take away a series of emotional and interpersonal obstacles, so that, allows members of the group to sewer their energy on the task of labour on which they make to accomplish. Therefore, the role of a manager, who is preoccupied to achieve good results for the company, is to develop the confidence of his employees in organisation, this thing being a path towards increased earnings. In this paper work we will refer at familiar actors who works together as part as same organisation.